The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s10815-013-0110-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical outcomes with respect to spermatozoan origin after artificial oocyte activation with a calcium ionophore

Abstract: Purpose Fertilization failures have occurred repeatedly in reproductive centers after intracytoplasmic sperm injection (ICSI) and artificial oocyte activation (AOA) has been used to prevent it. This study was performed to investigate whether spermatozoan origin influences clinical outcomes of AOAwith a calcium ionophore. Methods A total of 185 ICSI cycles with a history of no or low fertilization was included in this retrospective study. The outcomes of AOA after ICSI were compared with ejaculatednormal, ejacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…These findings indicate that neonatal outcomes in the ICSI-Ca versus ICSI protocol did not have obvious differences, regardless of normality or adverse consequences. A previous study demonstrated similar results regarding birth weight and gestational age (11). These findings might suggest that although the ICSI-Ca procedure involves additional manipulation on the oocyte, it does not have an effect on pregnancy outcome.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…These findings indicate that neonatal outcomes in the ICSI-Ca versus ICSI protocol did not have obvious differences, regardless of normality or adverse consequences. A previous study demonstrated similar results regarding birth weight and gestational age (11). These findings might suggest that although the ICSI-Ca procedure involves additional manipulation on the oocyte, it does not have an effect on pregnancy outcome.…”
Section: Discussionsupporting
confidence: 70%
“…One study included a cohort of 38 babies (20 singles and 18 twins in 29 cycles). All neonates were delivered after ICSI-Ca procedure, and no congenital birth defects were observed in this group (11). Vanden Meerschaut et al also evaluated 21 children ages 3-10 years who were born after AOA and found that they all lay within expected ranges regarding neurodevelopmental, intelligence, language, and communication skills (13).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The calcium ionophore A23187 (Sigma Chemical, Sigma, St Louis, MO, USA) was used for AOA, as previously described [ 5 ]. The final solution (10 µmol/L) was prepared prior to ICSI or IMSI.…”
mentioning
confidence: 99%
“…In a preliminary study, increased fertilization rates and significantly higher clinical pregnancy and implantation rates were achieved using AOA following ICSI compared with the previous treatment with standard ICSI in a group of patients who had experienced total fertilization failure or low fertilization rates (<50%) in their previous ICSI cycles. Furthermore, 38 healthy babies were delivered from 185 ICSI cycles by using AOA with a calcium ion [ 5 ]. These results support the safety of AOA with a calcium ionophore and suggest the effectiveness of AOA for ICSI cycles in patients with previous experiences of zero or low fertilization rates.…”
mentioning
confidence: 99%